(untitled) (International journal of medical sciences, 2026)
Type 3 diabetes mellitus is an emerging conceptual framework that links metabolic dysfunction with neurodegenerative processes, particularly Alzheimer’s disease. Unlike classical diabetes types that primarily affect peripheral glucose regulation, type 3 diabetes describes insulin resistance and relative insulin deficiency localized within the brain. This impairment disrupts neuronal glucose metabolism, leading to cellular energy deficits, oxidative stress, neuroinflammation, and progressive synaptic dysfunction. Central to this pathology is altered insulin signaling through the PI3K/Akt pathway, which contributes to amyloid-β accumulation, tau hyperphosphorylation, mitochondrial dysfunction, and neuronal loss. Epidemiological evidence indicates that individuals with type 2 diabetes have a significantly elevated risk of developing Alzheimer’s disease, supporting the hypothesis that metabolic and neurodegenerative pathways are closely interconnected. Understanding these mechanisms highlights the importance of insulin sensitivity, metabolic regulation, and anti-inflammatory strategies in preserving cognitive function. Although type 3 diabetes is not yet formally recognized as a clinical diagnosis, growing experimental and clinical data underscore its relevance in explaining Alzheimer’s pathophysiology and guiding future therapeutic approaches. Continued research may open new preventive and treatment strategies aimed at protecting brain health through metabolic intervention.